A multigene phylogenetic synthesis for the class Lecanoromycetes (Ascomycota): 1307 fungi representing 1139 infrageneric taxa, 317 genera and 66 families - Passo, Alfredo (2014)
The Lecanoromycetes is the largest class of lichenized Fungi, and one of the most species-rich classes in the kingdom. Here we provide a multigene phylogenetic synthesis (using three ribosomal RNA-coding and two protein-coding genes) of the Lecanoromycetes based on 635 newly generated and 3307 publicly available sequences representing 1139 taxa, 317 genera, 66 families, 17 orders and five subclasses (four currently recognized: Acarosporomycetidae,  Lecanoromycetidae, Ostropomycetidae, Umbilicariomycetidae; and one provisionarily recognized, Candelariomycetidae). Maximum likelihood phylogenetic analyses on four multigene datasets assembled using a cumulative supermatrix approach with a progressively higher number of species and missing data (5-gene, 5+4-gene, 5+4+3-gene and 5+4+3+2-gene datasets) show that the current classification includes non-monophyletic taxa at various ranks, which need to be recircumscribed and require revisionary treatments based on denser taxon sampling and more loci. Two newly circumscribed orders (Arctomiales and Hymeneliales in the Ostropomycetidae) and three families (Ramboldiaceae and Psilolechiaceae in the Lecanorales, and Strangosporaceae in the Lecanoromycetes inc. sed.) are introduced. The potential resurrection of the families Eigleraceae and Lopadiaceae is considered here to alleviate phylogenetic and classification disparities. An overview of the photobionts associated with the main fungal lineages in the Lecanoromycetes based on available published records is provided. A revised schematic classification at the family level in the phylogenetic context of widely accepted and newly revealed relationships across Lecanoromycetes is included. The cumulative addition of taxa with an increasing amount of missing data (i.e., a cumulative supermatrix approach, starting with taxa for which sequences were available for all five targeted genes and ending with the addition of taxa for which only two genes have been sequenced) revealed relatively stable relationships for many families and orders. However, the increasing number of taxa without the addition of more loci also resulted in an expected substantial loss of phylogenetic resolving power and support (especially for deep phylogenetic relationships), potentially including the misplacements of several taxa. Future phylogenetic analyses should include additional single copy protein-coding markers in order to improve the tree of the Lecanoromycetes. As part of this study, a new module (Hypha) of the freely available Mesquite software was developed to compare and display the internodal support values derived from this cumulative supermatrix approach.